2018
DOI: 10.1016/s2352-3026(18)30092-9
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemia and myeloid malignancy among people exposed to low doses (<100 mSv) of ionising radiation during childhood: a pooled analysis of nine historical cohort studies

Abstract: National Cancer Institute Intramural Research Program, National Cancer Institute, and US National Institutes for Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
90
2
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 31 publications
2
90
2
5
Order By: Relevance
“…Our study shows that compared with women in the general population of Israel, women with alopecia resulting from irradiation treatment for tinea capitis are at increased risk for serious physical conditions, with an especially high risk of developing migraines and cancer. Cancer prevalence has already been strongly associated with a history of childhood irradiation for tinea capitis [ 6 , 9 , 10 , 11 , 12 , 13 ]. Although studies have not specifically addressed the association of this childhood exposure with migraines, migraines are associated with early childhood trauma and adult stressful life events [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study shows that compared with women in the general population of Israel, women with alopecia resulting from irradiation treatment for tinea capitis are at increased risk for serious physical conditions, with an especially high risk of developing migraines and cancer. Cancer prevalence has already been strongly associated with a history of childhood irradiation for tinea capitis [ 6 , 9 , 10 , 11 , 12 , 13 ]. Although studies have not specifically addressed the association of this childhood exposure with migraines, migraines are associated with early childhood trauma and adult stressful life events [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until the introduction of the antifungal griseofulvin in 1958, about 200,000 children worldwide [ 6 ], mainly in the United States, Europe, and the Middle East [ 7 , 8 ], had been treated for tinea capitis by irradiation to induce epilation. Long-term follow-up studies have demonstrated the detrimental health effects of this treatment, including meningioma, leukemia, and tumors of the brain, salivary glands, thyroid, and skin, including melanomas in the head and neck area [ 6 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hematologic cancers are of concern to space exploration because these malignancies are known to be among the most radio-sensitive both in childhood and in adulthood. [18][19][20] We observed 4 hematologic cancers in the astronaut cohort when fewer than 2 were expected, for an SIR of approximately 200. While the 2 observed deaths from this cancer type represented an insigni cant reduction in the mortality rate, the expected number of deaths from this cancer exceeded the expected number of cases, making interpretation of the SMR di cult.…”
Section: Discussionmentioning
confidence: 90%
“…childhood leukaemia and central nervous system (CNS) tumours [1,2]. A number of environmental factors have been suggested that could partially explain cancer risks in the general population, including traffic-related air pollution [3], background radiation [2,4] and agricultural pesticides [5]. These risk factors vary in space and it is thus natural to expect spatial variation in childhood cancer incidence.…”
mentioning
confidence: 99%